2007
DOI: 10.1177/0305735607070305
|View full text |Cite
|
Sign up to set email alerts
|

Provoking the muse: a case study of teaching and learning in music composition

Abstract: This article reports the findings of a research project that investigated the nature of the teaching and learning process in music composition. Over the period of one semester, the formal interactions in one-on-one study sessions between an eminent composer-teacher and an experienced graduate student-composer were videotaped. Following the generation of video data, separate interviews were conducted with the composer-teacher and the student-composer in order to probe each of these participants’ perceptions of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
31
1
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 12 publications
1
31
1
1
Order By: Relevance
“…Due to the short-term nature of the school, the collaborative nature of teacher-student relationships, while present in a limited way, is less evident than in Barrett and Gromko's (2007) study, and there was little evidence of concern for students' developing "voice." The composerteachers in this study regarded their role as technical and cultural guides.…”
Section: Participant Reflectionscontrasting
confidence: 64%
See 1 more Smart Citation
“…Due to the short-term nature of the school, the collaborative nature of teacher-student relationships, while present in a limited way, is less evident than in Barrett and Gromko's (2007) study, and there was little evidence of concern for students' developing "voice." The composerteachers in this study regarded their role as technical and cultural guides.…”
Section: Participant Reflectionscontrasting
confidence: 64%
“…Building on studies of eminent composer-teachers working one-to-one with students in university settings (Barrett, 2006;Barrett & Gromko, 2007), it moves beyond tertiary training to investigate what many emerging composers regard as the next stage in their professional development: ensemble-based schools in which pieces are workshopped under the guidance of established, expert composers (Dahm & Isaacs, 2011;Gyger, 2014;Love & Barrett, 2014).…”
mentioning
confidence: 99%
“…Studies which have focused on the detailed 'reflection-in-action' at Higher Education level between teacher and student made possible in one-to-one tuition, have tended to conceptualise the musical development, professional and personal mentoring evident in this context in terms of apprenticeship (Rosenthal, 1984;L'Hommidieu, 1992;Gholson, 1998;Burwell, 2006;Barrett & Gromko, 2007), in keeping with the model of professional learning premised on collaborative reflection-in-action and reflection-on-action outlined by Schon (1983Schon ( , 1987). Schon's formulation of the dynamics of professional apprenticeship has been extremely influential and captures much of the power of the zone of proximal learning immediately evident, for example, in a musical masterclass.…”
Section: Introductionmentioning
confidence: 99%
“…2 As one-to-one tuition is so often the mainstay of a performer's education, particularly in the field of classical music, there is a strong rationale to consider the potential of mentoring within its practices. Research has suggested that one-to-one tuition may be conceptualised as a creative collaboration incorporating elements of mentoring (Barrett and Gromko 2007;Gholson 1998;L'Hommidieu 1992;Presland 2005). Evidence also suggests that it offers a powerful practical environment for learning and may stimulate reflective and reflexive learning (key elements of a mentoring process) (Burt and Mills 2006;Gaunt 2008Gaunt , 2010Kennell 2002;Purser 2005;Schmidt 1992).…”
Section: Mentoring and One-to-one Tuitionmentioning
confidence: 99%